PARONELLA ? OSTUNENSIS N. SP. FROM THE UPPER CRETACEOUS OF APULIA (SOUTHERN ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1989)
A new radiolitid rudist, Paronella ? ostunensis n. sp. from the Late Cretaceous of Apulia is described. The excellent preservation of the fossil material made possible to discuss the validity of the genus Paronella Wiontzek, 1934.
Keywords: Rudists; Taxonomy; Upper Cretaceous; Apulia.